Students’ Performance and Cognitive Skills in Chemistry Through Case-Based Learning Approach - Ricardo F. Uy Jr; Denis A. Tan (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: This study investigated the effects of a case-based learning (CBL) approach on academic performance and cognitive skills among Grade 9 students. Specifically, it aimed to determine the level of students’ academic performance in Chemistry as exposed to CBL and non-CBL; assess students' level of cognitive skills; ascertain significant differences in students' cognitive skills; find out the difference in the student's academic performance and determine the significant difference on students' level of knowledge retention. Method: The study employed a quasi-experimental research design using two comparable group classes. A validated teacher-made questionnaire was used to determine students' academic performance. The Gibson Cognitive Skill questionnaire was used to measure cognitive skills. Results: It was found that students in both groups had better academic performance in the post-test than in the pre-test. Students exposed to CBL performed better and scored higher than those under non-CBL. Meanwhile, students exposed to CBL had high cognitive skills, while those exposed to non-CBL had moderate cognitive skills. There was a significant difference in students' cognitive skills between CBL and non-CBL groups. Moreover, a significant difference existed in students' academic performance in the post-test and retention test between the two groups. Novelty: Recognizing the positive effect of case-based learning on students' performance, science teachers may consider integrating CBL as a practical alternative pedagogical approach to address the problem of lack of retention of science concepts.